Plant diversity in a nutshell: testing for small‐scale effects on trap nesting wild bees and wasps. Issue 2 (13th February 2014) - Fabian, Yvonne; Sandau, Nadine; Bruggisser, Odile T.; Aebi, Alexandre; Kehrli, Patrik; Rohr, Rudolf P.; Naisbit, Russell E.; Bersier, Louis-Félix
Abstract : Declining plant species richness in agro‐ecosystems and thus reduced habitat quality can have cascading effects on ecosystem functioning, leading to reduced pollination and biological control. Here we test if plant diversity can affect arthropod diversity and abundance on a very small scale, manipulating plant species richness (2, 6, 12 and 20 sown species) in small adjacent subplots (6 × 9 m) in 10 wildflower strips in an agricultural landscape. We simultaneously analyzed the effect of plant species richness, vegetation structure, and plant composition on the species richness and abundance of cavity‐nesting wild bees, wasps, their prey and natural enemies, and on the structure of their food webs. By separating the trap‐nesting species into functional groups according to their prey, we aimed to understand the underlying patterns for the effects of plant diversity. Increasing plant species richness had a significant effect only on spider‐predating wasps, the group of wasps trophically most distant from plants. In contrast, bees and food‐web structure were unaffected by plant diversity. Spider‐predating wasp abundance negatively correlated with the abundance of spiders, suggesting top‐down control. Interestingly, the abundance of spiders was the only variable that was strongly affected by plant composition. The hypothesis that the effect of plant diversity decreases with increasing trophic level is not supported by our study, and the mobility of species appears to play a greater role at this small spatial scale.